Foreign direct investment, efficiency, and total factor productivity: Does technology intensity classification matter? - Mohammad Zeqi Yasin; Dyah Wulan Sari (Universitas Islam Indonesia, 2022)
Purpose ― We examine whether the foreign direct investment (FDI) in promoting technical efficiency is controlled by the sector classifications based on the technology intensity (High Technology, Medium-High Technology, Medium-Low Technology, and Low Technology). Methods ― We use the Indonesian firm-level dataset of the large and medium manufacturing survey from 2007 to 2015 and employ the time-varying stochastic production frontier. Findings ― We reveal that FDI, technology intensity and absorptive Capacity significantly affect firms' production and efficiency. We also found that the Indonesian manufacturing industry from 2007 to 2015 experienced positive Total Factor Productivity growth, where High-Technology sectors experienced the largest magnitude among others. Meanwhile, technological progress stemming from FDI is enjoyed more by Low Technology sectors. Meaning to say, technology intensity classification does not matter to technological progress. Implication ― The host country's government should focus on industries with high technical capabilities to accelerate FDI gains for the firms. Simultaneously, human capital improvement also needs to be intensified, for instance, through training or human development, so that firms with lower technical capability can catch up and, consequently, receive similar benefits from FDI activities. Originality ― Our study accommodates the research gap by including the FDI effect in both productivity and efficiency in a single equation. Many studies merely categorize technology intensity following the stochastic production frontier estimation to obtain technical efficiency or TFP growth. In this sense, those studies did not control the impact of the technology-specific effect.